Leadership, Supervisory Practices, and Work Discipline as Determinants of Teacher Performance at MIN 2 Kerinci - Nurlatifa Salsa Tasnima; Yulasmi Yulasmi; Zefriyenni Zefriyenni; Masrida Zasriati (Al Dzahab, 2026)
Purpose: This study aims to examine the influence of leadership, supervisory practices, and work discipline on teacher performance at MIN 2 Kerinci. Specifically, it seeks to determine how each of these factors individually affects teacher performance and to what extent they collectively contribute to enhancing overall teaching effectiveness. The study also intends to provide empirical evidence for educational policymakers and school administrators to develop strategies for improving teacher performance in the school context. Design/Methodology/Approach: The research employed a census sampling technique, involving all 87 teachers at MIN 2 Kerinci. Primary data were collected through questionnaires distributed to the teachers. Data analysis was conducted using multiple linear regression with the assistance of SPSS software. Findings: The results indicate that: (1) leadership has a negative and non-significant effect on teacher performance; (2) supervisory practices have a positive and significant effect on teacher performance; (3) work discipline has a positive and significant effect on teacher performance; and (4) collectively, leadership, supervisory practices, and work discipline account for 74.9% of the variance in teacher performance, with the remaining 25.1% influenced by other factors outside this study. Research Implications: These findings suggest that improving supervisory practices and work discipline can enhance teacher performance, while leadership style may require further investigation to understand its impact. Educational policymakers and school administrators can use these insights to develop strategies for optimizing teacher effectiveness.